The Reluctant And The Compliant: Elite Competition, Social Cleavage, And The Domestic Limits Of Great-Power Compellence - Yohanes Sulaiman (Jurnal Dinamika Global, 2026)
Why do some weak states give in to a great power's demands while others, just as exposed, refuse and gain at home for refusing? This article puts the answer in the target's domestic politics rather than in the coercer's strength. A foreign demand does not reach a single government adding up costs and benefits; it drops into a running fight among elites, where any concession can be picked up by a rival and used as a weapon. Whether that danger is real depends on two things: how secure the regime is, and whether the demand touches a social cleavage an opposition can mobilize. I develop the argument through three responses to the United States tariff campaign of 2025. Indonesia and Vietnam complied within weeks; Brazil refused, and its president's standing rose. Power barely varied across the three. Their domestic politics did.